Acute Pancreatitis in a Previously Exocrine Pancreatic Insufficient Cystic Fibrosis Patient Who Had Improved Pancreatic Function After Being Treated With Lumacaftor/Ivacaftor. Issue 3 (12th August 2021) - Redman, Alexander W.; Yoo, Michelle; Freswick, Peter; Thompson, Karen
Abstract : Exocrine pancreatic insufficiency (EPI) is a common complication of cystic fibrosis (CF). While previously considered to be irreversible, recent reported cases document improved pancreatic function in CF patients with mild mutations after ivacaftor treatment alone. We report a 12-year-old female with homozygous F508del CF and EPI who developed acute pancreatitis after 3 years on lumacaftor/ivacaftor and subsequently had improved pancreatic function. As CF therapies advance, some EPI CF patients with more severe CF transmembrane conductance regulator mutations may see improved pancreatic function and subsequently develop pancreatitis.